PENGARUH CAPITAL INTENSITY, MANAJEMENEN LABA, DIVERSITAS GENDER TERHADAP TAX AVOIDANCE - Galuh Randy Ray (2022)
This study aims to determine the effect of capital intensity, earnings management and gender diversity on tax avoidance with profitability as a kontrol variable. In this study, the population is the Manufacturing sector companies listed on the IDX during the period 2018 to 2020. This study uses the Purposive Sampling technique so as to obtain a sample of 144 companies. The hypothesis in this study was tested using the technique of Multiple Linear Regression Analysis with a significance level of 10%. The results obtained from this study are that Capital Intensity has no effect on Tax Avoidance, AbnCFO has a negative effect on Tax Avoidance, AbnPROD has a negative effect on Tax Avoidance, AbnDISX has no effect on Tax Avoidance, Gender Diversity has an effect on Tax Avoidance, Profitability has a positive effect on Tax Avoidance. Keywords: Tax Avoidance, Capital Intensity, Earning Management, Diversitas Gender, and Profitability.